From androcentrism to relationality - Irarrázaval, Diego (2001)
The experience and reflection of gender deals with the details of each day and the great human dilemmas. We feel it in the body and in the power schemes. She touches the cultural, the political, the spiritual, the affective, the relationship with the environment. The issue of gender corresponds to men and women (it is therefore not a "feminine issue"). It is about a transforming perspective and action of human relations and historical forms; are relevant factors for theology and spirituality. This is what I want to find out.